TMIC-02. INTERACTION OF LIGAND CONJUGATED QUANTUM DOTS WITH THE GLIOMA STEM CELL SECRETED EXOSOMES AND SUBSEQUENT UPTAKE BY THE GLIOMA STEM CELLS OF VARIOUS SUBTYPES. (5th November 2018) - Madhankumar, A B; Mrowczynski, Oliver; Slagle-Webb, Becky; Thomas, Abraham; Zacharia, Brad; Mintz, Akiva; Connor, James
Abstract: Glioblastoma tumors are known to secrete an enormous number of exosomes with various molecular signatures. Some recent studies also demonstrate that the exosomes secreted by the glioma initiating cells or glioma stem cells carry differentially expressed mRNA, miRNA and protein that would impart radiation and chemo-resistance to the adjacent non-stem cancer cells. It is important to investigate the exosome secretion profile by the cancer stem cells and their re-uptake profile by the glioma cells belonging to various subtypes in the vicinity of tumor. In our earlier study we identified that exosomes from glioma stem cells express a tumor associated IL13Rα2 that could bind with interleukin 13 conjugated quantum dots (QD), which can be subsequently profiled by various physico-chemical methods. In our recent investigation we observed that a mutated form of IL-13, TQM13, can be conjugated with QD and can complex with exosomes. These QD-bound exosome can subsequently be monitored by fluorescent microscopy utilizing the intrinsic fluorescence property of the quantum dots. In our present investigation, TQM13-QD was complexed with exosomes that originated from glioma stem cells from mesenchymal (T387) and proneural (T3691) subtypes. Various glioma cell lines such as U87, T3691 and T387, and Jurkat cells, an immortalized T-lymphocyte cells, were then treated with the TQM13-QD:exosome complex. Our investigation revealed that cells had a higher uptake of the TQM13-QD upon complexation with exosomes when compared to quantum dots without exosome complexation. In vivo experiments were subsequently performed by injecting T3691 exosomes complexed with TQM13-QD in U87-Luc cells which were implanted as an orthotopic glioma tumor mouse model. Intravital imaging spectroscopy (IVIS) images confirmed the localization of TQM13-QD: exosome complex in the tumor region as early as 60 minutes post injection. Current studies are investigating the mechanism of uptake of TQM13-QD complexed with fluorescently labeled exosomes and quantifying their uptake.